A new weird cricket (Orthoptera, Gryllidea) from mid-Cretaceous Kachin amber in northern Myanmar - Xia Ji; André Nel; Chuantao Xiao; Andrej V. Gorochov; Edmund A. Jarzembowski; Zehao Ma; Chunpeng Xu (Fossil Record, 2025)
Gryllidea, one of the most species-rich groups in Orthoptera, are characterized by relatively scarce fossil records until the K-Pg extinction. This study describes a unique Mesozoic cricket, Fortigryllus xiangrui gen. et sp. nov., based on a well-preserved specimen from mid-Cretaceous Kachin amber in northern Myanmar. It exhibits very peculiar morphologies including fore-, mid-, and hindlegs nearly equal in robustness, and exceptionally stout femora in all three pairs of legs. Although it has some putative synapomorphies with the Phalangopsidae, the lack of information on the genital characters forbid us to accurately attribute it to a precise family. Crawling is tentatively proposed as a mode of locomotion in this Mesozoic cricket. This new find reveals a novel morphology in Cretaceous crickets and suggests a great potential biodiversity of crickets in this mid-Cretaceous ecosystem.